2021
DOI: 10.1101/gad.348422.121
|View full text |Cite
|
Sign up to set email alerts
|

Features and mechanisms of canonical and noncanonical genomic imprinting

Abstract: Genomic imprinting is the monoallelic expression of a gene based on parent of origin and is a consequence of differential epigenetic marking between the male and female germlines. Canonically, genomic imprinting is mediated by allelic DNA methylation. However, recently it has been shown that maternal H3K27me3 can result in DNA methylation-independent imprinting, termed "noncanonical imprinting." In this review, we compare and contrast what is currently known about the underlying mechanisms, the role of endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 114 publications
1
59
0
Order By: Relevance
“…Canonical genomic imprinting relies on allele-specific DNA methylation (see [56] for a recent review), and such mechanism was initially proposed to underlie iXCI as well [33][34][35]. Contrary to these early hypotheses, however, later studies with DNA methyltransferase maternal knockout embryos ruled out DNA methylation as having a role in setting the imprint [57].…”
Section: The Unexpected Outcome: a Non-canonical Maternal Imprintmentioning
confidence: 99%
“…Canonical genomic imprinting relies on allele-specific DNA methylation (see [56] for a recent review), and such mechanism was initially proposed to underlie iXCI as well [33][34][35]. Contrary to these early hypotheses, however, later studies with DNA methyltransferase maternal knockout embryos ruled out DNA methylation as having a role in setting the imprint [57].…”
Section: The Unexpected Outcome: a Non-canonical Maternal Imprintmentioning
confidence: 99%
“…The KRAB-ZFPs are evolutionarily diverse proteins that protect against the insertion of retroviruses (Macfarlan et al, 2012;Rowe et al, 2013), demonstrating that another host defense mechanism against retroviruses also exists and is functional in the maintenance of genomic imprinting memories (Edwards et al, 2019;Ondičova et al, 2020;Hanna and Kelsey, 2021). Thus, accumulating evidence indicates a close relationship between genomic imprinting and the insertion of retroviruses and LTR retrotransposons, as originally proposed in the host defense hypothesis.…”
Section: Molecular Mechanisms Underlying Gdmr Maintenance In Pre-and ...mentioning
confidence: 91%
“…Recent work has shown that the gDMRs are established as a consequence of differential responses to the invading DNAs in the oocytes and prospermatogonia as well as to afford subsequent protection from DNA demethylation in preimplantation development (see the next section). Discovery of the oocyte-specific transcripts spanning the gDMRs has provided an important clue to the mechanism of the establishing of the maternal gDMRs (Chotalia et al, 2009;Veselovska et al, 2015;Smallwood et al, 2011;Hanna and Kelsey 2021). In oocytes, DNA methylation is exclusively on active gene body regions, including the maternally imprinted gDMRs (Kobayashi et al, 2012).…”
Section: Molecular Mechanisms Underlying the Establishment Of Differe...mentioning
confidence: 99%
“…A classic example of this phenomenon is genomic imprinting, where a single parental allele, either the maternal or paternal, is programmed by the gametes to be transcribed in somatic cells of the offspring, while the other allele is silent. This group includes many genes, such as Igf2 and Snrpn, which appear to play some role in early embryonic growth control and have been found to be involved in a number of genetic diseases (Hanna and Kelsey, 2021).…”
Section: Monoallelic Expressionmentioning
confidence: 99%